The Kuntilanak Image in Mangkujiwo Movie: Roland Barthes Semiotics Analysis - Sania Safira Luniar; Poppy Febriana (Indonesian Journal of Cultural and Community Development, 2022)
Many of Indonesia's horror films raise myths that are very strong among the public, such as the myth about the Kuntilanak ghost. Kuntilanak, the ghost of a woman who is pregnant is often featured in films, this ghost is often described as a ghost who has a lot of grudges and is usually abused by irresponsible people such as being used for pesugihan. By researching the film Mangkujiwo, which tells how the Kuntilanak ghost was born. This study also aims to describe how Kuntilanak is portrayed in the film both during his life and after becoming a Kuntilanak ghost figure. The type of research used in this research is descriptive qualitative, this research uses Roland Barthes' semiotic research methods, markers, signifiers that exist at the denotative and connotative levels. In addition, data collection was carried out by means of observation and documentation. The results showed that the image of Kuntilanak in the film Mangkujiwo shows the existence of violence both physically, mentally and sexually, spiritually, besides that it also shows that during his life he was described as a comfort woman and even used as a sacrifice for knowledge. black. Where the violence is mostly done by the figure of Kuntilanak both before and after death.